The Use of Artificial Intelligence in The Development of Vision Aids for The Visually Impaired - Lukman, Lukman; Bakti, Rizky Yusliana; Angreani, Desy; Alamsyah, Muh. (Riwayat: Educational Journal of History and Humanities, 2025)
The development of assistive technologies for the visually impaired has gained significant attention in recent years, with Artificial Intelligence (AI) playing a key role in advancing vision aids. This study explores the use of AI in enhancing the functionality and accessibility of vision aids for the visually impaired through a qualitative, literature-based approach. By reviewing existing studies and research on AI-powered devices such as smart glasses, object recognition systems, and AI-guided navigation tools, this paper identifies how AI contributes to improving the quality of life for individuals with visual impairments. The study highlights key AI technologies, including computer vision, machine learning, and natural language processing, that allow devices to provide real-time information about the surrounding environment, recognize objects, and assist with daily tasks. Furthermore, this paper discusses the challenges of developing AI-based vision aids, such as technological limitations, user acceptance, and affordability, while emphasizing the need for interdisciplinary collaboration in creating more effective solutions. The findings suggest that AI has the potential to significantly enhance the independence of visually impaired individuals by enabling smarter, more responsive assistive devices. Future research is recommended to focus on empirical studies, long-term user experiences, and the ethical considerations surrounding AI use in assistive technologies.